Design of a System with a Potential Application to Neonatal Jaundice Phototherapy - Contreras-Álvarez, V. H.; González-Landaeta, R. E.; Chapa-González, C. (Revista Mexicana de Ingenieria Biomedica, 2017)
This project consisted in the design and construction of a prototype with potential application to a phototherapy system for neonatal jaundice using for the first-time high power 10 W LEDs. The methodology for the design of different electronic circuits which were used for feeding the drive current of the LEDs, the current control method described using pulse width modulation (PWM) generated by the known 555 integrated circuit is described. The printed circuit board was designed with the help of the Orcad Layout simulator. Two high-power 10 W LEDs were used for maintaining the intensity required for the treatment, minimizing the space used by the number of LEDs used in the conventional equipment. Among the limitations presented in this research was the use of the Arduino platform, due to several improve that can be used to improve and increase the use of this microcontroller, and in this way to digitize the system, reducing the circuitry of control. The prototype presented meets the requirements for a phototherapy system according to the different references used.